2010
DOI: 10.1111/j.1365-2699.2009.02245.x
|View full text |Cite
|
Sign up to set email alerts
|

A modern pollen–climate calibration set based on lake sediments from the Tibetan Plateau and its application to a Late Quaternary pollen record from the Qilian Mountains

Abstract: Aim  Fossil pollen spectra from lake sediments on the Tibetan Plateau have been used for qualitative climate reconstruction, but no modern pollen–climate calibration set based on lake sediments is available to infer past climate quantitatively. This study aims to develop such a dataset and apply it to fossil data. Location  The Tibetan Plateau, between 30 and 40° N and 87 and 103° E. Methods  We collected surface sediments from 112 lakes and analysed them palynologically. The lakes span a wide range of mean an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
100
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 51 publications
9
100
1
Order By: Relevance
“…Besides having consistent taxonomy and nomenclature and being of comparable quality, the modern biological data should be from the same sedimentary environment (e.g. lakes of similar size) as the fossil data-sets used for reconstruction purposes (Herzschuh et al 2010a). Recent developments in modelling pollen-source areas (e.g.…”
Section: General Limitations Of Climate Recons-tructionsmentioning
confidence: 99%
“…Besides having consistent taxonomy and nomenclature and being of comparable quality, the modern biological data should be from the same sedimentary environment (e.g. lakes of similar size) as the fossil data-sets used for reconstruction purposes (Herzschuh et al 2010a). Recent developments in modelling pollen-source areas (e.g.…”
Section: General Limitations Of Climate Recons-tructionsmentioning
confidence: 99%
“…However, significant discrepancies exist among different proxy records; in particular, pollen and ostracod oxygen isotope (δ 18 O) records indicate different periods for the climatic optimum during the Holocene (Lu et al 2010;. Pollen records from Qinghai Lake and the surrounding lakes of the northeastern Tibetan Plateau suggest a relatively dry early Holocene, with the wettest period spanning the middle Holocene, and then another dry period in the late Holocene Herzschuh et al 2010;Cheng et al 2013;Wang et al 2014a). Pollen-based moisture changes lag the Northern Hemisphere June insolation maxima by ~3 ka.…”
Section: Introductionmentioning
confidence: 99%
“…The deciphering of fossil pollen data must be performed on the basis of the investigation of modern pollen assemblages. Numerous studies (e.g., Wright et al, 1967;Gaillard et al, 1992;Sugita, 1994;Cour et al, 1999;Davis, 2000;Shen et al, 2006;Ma et al, 2008;Zhao and Herzschuh, 2009;Herzschuh et al, 2010;Lu et al, 2011;Fall, 2012;Zheng et al, 2013;Tian et al, 2014) have been conducted to understand the relationship of modern pollen assemblages with contemporary vegetation and climate. Modern pollen assemblages are mainly collected from airborne pollen collectors (e.g., Cour et al, 1999;Giesecke et al, 2010), moss polsters (e.g., Hicks and Birks, 1996;Mazier et al, 2006), topsoils (e.g., Xu et al, 2009;Zhang et al, 2010) and surface lake sediments (e.g., Herzschuh, 2007;Seppa et al, 2004).…”
mentioning
confidence: 99%
“…Herzschuh (2007) investigated the modern pollen assemblages of 113 lakes, and established a surface lake sediment pollen database in the northeastern Tibetan Plateau. Based on this database, Herzschuh and her colleagues (Herzschuh et al, , 2010 developed pollen-climate transfer functions for the northeastern Tibetan Plateau, and used the transfer functions to quantitatively reconstruct the Holocene climatic changes in Lakes Koucha , Luanhaizi (Herzschuh et al, 2010) and Ximencuo . Tian et al (2014) reported the pollen assemblages from surface lake sediments of 90 lakes in central-western Mongolia.…”
mentioning
confidence: 99%